Welcome to paradise: Measuring vegetation responses to tourism and agricultural activity using Leaf Area Index in the Galapagos Islands - Lauren A. Rhodes; Julio E. Tinoco; Gonzalo E. Sánchez; Bernard Moscoso (PLoS ONE, 2026)
The Galapagos Islands are globally recognized for their biodiversity, yet the high volume of annual visitors and dependence on food imports raise significant concerns regarding human-induced environmental pressure. The COVID-19 pandemic resulted in a complete halting of tourism and extreme mobility restrictions, presenting a unique natural experiment to quantify how the abrupt reduction of human activity affects vegetation. This study provides the first joint assessment of how the tourism and agricultural sectors reacted in tandem to this mobility shock. Using satellite-based Leaf Area Index (LAI) data and a doubly robust difference-in-differences approach, we examine vegetation density shifts across both touristic and agricultural zones. Our findings reveal a significant 51% increase in vegetation density within tourism areas, specifically the fragile Bushes and Cacti zones, following the cessation of foot traffic. Concurrently, we document a 33% increase in LAI within agricultural zones relative to the counterfactual, signaling an intensification of local production. Further, these structural shifts in vegetation density persisted even as initial restrictions were eased. These quantitative results offer novel insights into the rapid responsiveness of island landscapes to changes in the human footprint, providing a data-driven foundation for resilient land-use policy.